Dynamic filtration at soil-geotextile interfaces - Khan, Muhammad Waleed (2017)
The soil-geotextile filtration mechanism is a complex process which depends on physical compatibility between the geotextile and the soil to be retained. Geotextiles often perform well under steady state conditions like those found in dams. However, when the soil-geotextile interface is subjected to dynamic loading, the requirements for successful filtering are uncertain and/ or conservative as the controlling factors are not well understood in these circumstances. There are few filter design criteria available for dynamic flow conditions. These criteria do not properly address the internal instability of soils for which the rearrangement of particles adjacent to the filter interface is complex. Unstable soils may exist in roadway bases adjacent to pavement edge drain. Therefore, this research work was carried out to better understand the filtration behaviour of non-woven geotextiles with internally stable and unstable soils beneath roads. To carry out the filtration tests, a flexible wall gradient ratio (GR) apparatus was developed. The GR tests were performed to investigate the effect of different factors on the filtration performance of the soil-geotextile interface under dynamic conditions. The factors included hydraulic gradient, vertical stress and frequency of loading, soil gradation and geotextile properties. Test results were interpreted in terms of head loss within the soil and across the geotextile, GR values, permeability ratio, mass and gradation of particles passed through geotextiles, microscopic images of geotextiles after test, partial geotextile clogging levels and hydrometer sieve analyses of soil samples to compare the gradation of samples after test with the original gradation. All the tests were performed under a hydraulic gradient of five. The internal stability of soil samples were evaluated by three geometric criteria. The test results showed that a high hydraulic gradient has the ability to lead to the internal instability of soils which resulted in migration of fines towards the geotextiles. The dynamic loading resulted in increase of soil migration within the base soil as well as washing out of soil particles through geotextiles. No significant effect of increase in frequency and vertical stress was observed on filtration behaviour of soil-geotextile combinations. The geotextile pore size was found to be the main factor controlling the filtration behaviour as compared to other geotextile properties. The Kenney and Lau (1985) and the Kezdi (1979) criteria predicted well the internal instability of soils under dynamic conditions. In this research study, a new method was suggested which is able to measure the pore sizes along the entire thickness of geotextiles. The filtration tests showed that geotextiles having the same large openings but different pore size distributions may result in different filtration performances. Based on the test results, filter design criteria were suggested for piping and blinding limits which were compared with the existing design criteria. These new filter criteria were found to be more appropriate in terms of piping and blinding limit states.